Analysis of Health Management Strategies in Improving Hospital Service Quality: Literature Review - Nadia Amanda Azwa; Assyifa Deswita Mrp; Eva Sahriani Sikumbang; Nadhilah Hasibuan; Ade Ilham Kesuma; Sayyidati Zahira; Sri Rahayu; Nur Hasanah; Wasiyem (Universitas Muhammadiyah Palu, 2025)
Hospital services today face increasing public demands for fast, safe, and high-quality care. To meet these challenges, an appropriate, integrated, and sustainable health management strategy is required. This study aims to analyze effective health management strategies for improving the quality of hospital services through a systematic literature review. The method used is a Systematic Literature Review (SLR), examining 15 Indonesian-language scholarly articles from Google Scholar published between 2020 and 2025. From the selection process, 8 articles met the inclusion criteria and were further analyzed based on managerial strategies and their impact on service quality. The findings show that strategies such as thorough planning, strengthening human resources, implementation of Hospital Management Information Systems (HMIS), and quality evaluation methods such as Total Quality Management (TQM), Kaizen (5R), and FMEA play a significant role in improving service quality. The application of international standards such as ISO 9001:2015, enhanced communication, and regular evaluations using quality indicators and the Balanced Scorecard also contribute substantially. In conclusion, a combination of integrated management strategies focused on continuous improvement has proven effective in creating optimal, efficient, and competitive hospital service quality.